“Utilization of White Ginger (Zingiber Officinalee Rosc) as Natural Food Ingredients," - Ruksanan; Hastian (International Journal of Management and Education in Human Development, 2022)
This study aims to explore the processing of candied ginger and observe the effect of adding citric acid and storage time to candied ginger produced. The treatment applied in the manufacture of candied ginger is the interaction of the addition of citric acid and storage time on the quality of candied ginger. Parameters observed for candied ginger produced include Water content and reducing sugar content. Total acid, as well as organoleptic tests on the value of taste, color, and texture value. The experimental design used was a completely randomized design (CRD). The results showed that the addition of citric acid greatly affected the water content, reducing the sugar content and total acidity of candied ginger. In the treatment interaction, the more addition of citric acid and the longer the storage, the water content, total acid, and texture increased, on the other hand, the reduced sugar content, taste, and color produced decreased. In organoleptic testing, the most preferred taste of candied ginger was the addition of 1% citric acid and a storage time of 0 days (3.60). The most preferred color was the addition of 1.5% citric acid and 0 days of storage (4.08) while the most preferred texture value was the addition of 2% citric acid and 6 days of storage with a panelist assessment score of 3, 88 ( Like ). In conclusion, Ginger can be used as candied fruit with a concentration according to the concentration with the value of the level of preference according to the needs of each with the addition of citric acid according to the needs of the organoleptic values ​​that are expected to be carried out.